2021
DOI: 10.1002/ange.202015362
|View full text |Cite|
|
Sign up to set email alerts
|

Sterilizing Immunity against SARS‐CoV‐2 Infection in Mice by a Single‐Shot and Lipid Amphiphile Imidazoquinoline TLR7/8 Agonist‐Adjuvanted Recombinant Spike Protein Vaccine**

Abstract: The search for vaccines that protect from severe morbidity and mortality because of infection with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), the virus that causes coronavirus disease 2019 (COVID‐19) is a race against the clock and the virus. Here we describe an amphiphilic imidazoquinoline (IMDQ‐PEG‐CHOL) TLR7/8 adjuvant, consisting of an imidazoquinoline conjugated to the chain end of a cholesterol‐poly(ethylene glycol) macromolecular amphiphile. It is water‐soluble and exhibits massive tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Our TLR agonist additions to AddaS03-like emulsions resulted in high ACE2 binding inhibition, but their equivalence to the AddaS03-like emulsion suggests that TLR agonist addition is not necessary for nAb production here. Previous results using delivery vehicles other than emulsions suggested that a TLR4 or TLR7/8 agonist, alone or in combination, produced robust nAb titers [ 79 , 80 , 81 , 82 , 83 ]. The TLR4 agonist Monophosphoryl Lipid A demonstrated a production of effective nAb titers comparable to that of AddaVax when used to adjuvant recombinant RBD [ 79 ], though combinations of the two were not tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our TLR agonist additions to AddaS03-like emulsions resulted in high ACE2 binding inhibition, but their equivalence to the AddaS03-like emulsion suggests that TLR agonist addition is not necessary for nAb production here. Previous results using delivery vehicles other than emulsions suggested that a TLR4 or TLR7/8 agonist, alone or in combination, produced robust nAb titers [ 79 , 80 , 81 , 82 , 83 ]. The TLR4 agonist Monophosphoryl Lipid A demonstrated a production of effective nAb titers comparable to that of AddaVax when used to adjuvant recombinant RBD [ 79 ], though combinations of the two were not tested.…”
Section: Resultsmentioning
confidence: 99%
“…The TLR4 agonist Monophosphoryl Lipid A demonstrated a production of effective nAb titers comparable to that of AddaVax when used to adjuvant recombinant RBD [ 79 ], though combinations of the two were not tested. In another study, an imidazoquinoline TLR7/8 agonist linked to an amphiphile, induced nAbs that more effectively neutralized SARS-CoV-2 than AddaVax, each after one dose [ 80 ]. The vaccine formulation Covaxin, which chemisorbs an imidazoquinoline TLR7/8 agonist to particulate aluminum hydroxide, demonstrated efficacious neutralizing activity against SARS-CoV-2 variants in humans [ 81 , 82 ] and as a result, the World Health Organization issued the vaccine for emergency use [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can self-assemble into micelles in aqueous solutions and be used as a liposome, which has applications in drug delivery, bioimaging, and nanomedicine. [30][31][32][33] Therefore, the selenide linker was employed as an oxidation-responsive constituent within the PEG and cholesterol moieties to fabricate ROS-sensitive lipid nanoparticles. SBL was alcoholized with mPEG2000 to obtain selenol in situ, followed by nucleophilic addition with electron-deficient acrylated cholesterol to give PEG-Se-Chol in one pot.…”
Section: Mechanism Of the Unsymmetric Selenide Oxidation Elimination ...mentioning
confidence: 99%
“…127 In addition, the combination of TLR7/8 agonist resiquimod/R848 with spike protein vaccine/ inactive virus increases IgG antibody titers and potentiates anti-SARS-CoV-2 infection in vivo. [141][142][143] In a phase II clinical trial, administration of TLR8 ligand selgantolimod/GS-9688 helps control virally suppressed adult patients with chronic hepatitis B. 144 The administration of TLR8 ligand motolimod/VTX-2337 can improve papillomavirus positive SCCHN.…”
Section: Tlr8 and Vaccinationmentioning
confidence: 99%